The Effect Of Giving Green Bean Juice On Hemoglobin Levels In Pregnant Women With Mild Anemia In The UPTD Area Of Alasa Health Center In 2023 - Lubis, Anita Damayanti; Handayani, Purnama (Sean Institute, 2024)
Pregnancy and childbirth are natural processes for a woman. Pregnancy results in an increase in blood volume which can cause anemia. One alternative that can be done to prevent anemia in pregnant women is by giving green bean juice. This study aims to determine the effect of giving green bean juice on hemoglobin levels in mildly anemic pregnant women in the UPTD area of the Alasa Health Center in 2023. This research is a pre-experimental design research with a one group pretest and posttest design approach. This research was carried out from 2 October 2023 to 14 October 2023. The population was 58 people. Sampling used purposive sampling with a sample size of 20 people. The research results showed that the hemoglobin level in mildly anemic pregnant women before being given green bean juice in the UPTD area of Alasa Health Center was mild anemia and the hemoglobin level in mildly anemic pregnant women after being given green bean juice in the UPTD area of Alasa Health Center was normal. Based on the results of the paired t-test, the p value = 0.001 <0.05. The conclusion of this research is that there is an effect of giving green bean juice on hemoglobin levels in mildly anemic pregnant women in the UPTD Alasa Health Center area in 2023. Suggestions in this research are that UPTD Alasa Health Center provides education and information to pregnant women. Apart from consuming Fe tablets, mothers can also consume Fe tablets. green bean juice for preventing anemia.